ANALISIS KELAYAKAN BISNIS KOAGULAN BERBASIS LIMBAH GARAM (BITTERN) SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH PETANI GARAM - Agustine, Dian Ayu Dwi Permata; Nugroho, Prasetyo; Susandini, Aprilina; Arfy, Widya Rizka (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the business feasibility of utilizing salt waste (bittern) as a raw material for making magnesium chloride coagulant to increase the economic value of salt farmers in Bunder Village, Pademawu District, Pamekasan Regency, Madura. The study uses a quantitative descriptive method through surveys, field observations, and interviews with salt farmers and related agencies. Analysis was carried out on the cost structure, income, revenue, and financial feasibility indicators including Break Even Point (BEP), Payback Period (PP), Revenue Cost Ratio (R/C Ratio), Benefit Cost Ratio (B/C Ratio), and Net Present Value (NPV). The results showed that the total annual production cost was Rp. 39,457,200, the cost of production was Rp. 15,800 per liter, and the selling price was Rp. 35,000 per liter, resulting in a net income of Rp. 48,042,800 per year. The break-even point (BEP) value was achieved at a volume of 635 liters, with a PP of 0.70 years (8 months), a return to market ratio of 2.21, a return to market ratio of 1.21, and a positive NPV of Rp 31,047,791.27. Based on these results, the bittern-based coagulant business is declared financially and economically feasible and has the potential to support the development of a sustainable salt industry and environmentally friendly waste management in the coastal areas of Madura.